Performance of Local Government Determinants in Indonesia: The Moderating Role of Government Internal Control System - Chaerani, Eva Yunadia; Wibowo, Puji (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2025)
The purpose of this research is to examine the impact of the level of corruption, the level of independence, and audit findings on local government achievement, by considering the maturity of the government internal control system (SPIP) as a moderating variable. This research uses a quantitative approach with ordinal logistic regression analysis techniques. The total research sample consists of 33 Indonesian provinces in the period 2018-2022. The results showed that the level of independence had a positive impact and audit findings had a negative impact on the performance of sub-national governments, while the level of corruption had no effect on local government performance. In addition, SPIP maturity does not moderate the association between the explanatory variables and the explained variable. This study suggests that the central government needs to fulfill periodic SPIP maturity assessments by local governments and conduct evaluations of the SPIP maturity assessment. Local governments are also advised to strengthen the role of the inspectorate and be more optimal in reviewing sources of revenue. Keywords: Local Government Performance; Level of Corruption; Level of Independence; Audit Findings; SPIP maturity.